Associations between dietary intake of B vitamins and cardiovascular risk factors in elderly men: A cross‐sectional study. Issue 10 (15th August 2021) - Mozaffari, Hadis; Askari, Mohammadreza; Bellissimo, Nick; Azadbakht, Leila
Abstract: Objective: Low intake of B vitamins can lead to hyperhomocysteinaemia, which is reported as a risk factor for cardiovascular disease (CVD). However, little is known about this relationship. Therefore, we decided to examine the association between dietary intake of B vitamins and cardiovascular risk factors in elderly men. Methods: The present cross‐sectional study consisted of 357 elderly men. Dietary intake was assessed using a validated and reliable food frequency questionnaire. All biochemical factors [fasting blood sugar (FBS), triglyceride (TG), high‐sensitivity C‐reactive protein (hs‐CRP), interleukin 6 (IL‐6) and tumour necrosis factor‐α (TNF‐α)], waist circumference (WC) and blood pressure (BP) were assessed using standard methods. Results: A significant inverse association was observed between high dietary intake of total B vitamins (ORTotal B vitamins : 0.30; 95% CI: 0.10, 0.86; P  = .01) and vitamin B9 (ORvitamin B9 : 0.20; 95% CI: 0.02, 0.52; P  = .002) with high WC. Furthermore, an inverse association was observed between high dietary intake of vitamin B6 (ORvitamin B6 : 0.28; 95% CI: 0.08, 1.00; P  = .05) and vitamin B9 (ORvitamin B9 : 0.20; 95% CI: 0.06, 0.70; P  = .01) with hs‐CRP level. Conclusions: In elderly men, a high dietary intake of total B vitamins and vitamin B9 was associated with lower odds of having a high WC. Similarly, high dietary intake of vitamin B6 and B9 was associated with lower odds of having a high hs‐CRP level.